Kajian Pengembangan Kawasan Agrotechnopark di Sumatera Utara - Kuswardani, Retna Astuti; Simanullang, Endang Sari; Siregar, Nina Salmaniah (Universitas Medan Area, 2013)
The proposes of this research are to find out some criteria of agrotechnopark’s area, as a description of a potential region for the agrotechnopark’s development, agrotechnopark area’s management of development and the development strategy of agrotechnopark area’s in North Sumatera. Some of area is used as a sample for this research are integral animal husbandary and the crop of food’s area in the village of Sei Buluh, Serdang Bedagai Regency, integral animal husbandary and the crop of horticulture’s area in the village of Jarang Uda, Karo Regency, integral fresh water fishery cultivation’s area in the village of Selotong, Langkat Rgency, Yayasan Ekosistem Lestari’s Agrotechnopark area, The village of Timbang Lawan, Langkat Regency. The result of the research showing that the some of integral area is reasonable to develop be a agrotechnopark area based on the criteria of technical, economical and social. the development of agrotechnopark’s region must be looking of physical’s potential, finance and develpment’s program is related with agricultural, animal husbandary and fishery’s sector. The development management of agrotechnopark’s area is needed as a planning (product and infrastructure), process and evaluation. The development strategy of agrotechnopark’s area is analyzed by internal analysis (strength and weakness) inside a current agrotechnopark’s area and external analysis (Opportunity and Threats) outside a current agrotechnopark’s area. This research is recommended that integral animal husbandary and the crop of food’s area in the village of Sei Buluh, Serdang Bedagai Regency is a pilot project to be a agrotechnopark’s area in North Sumatera, arranging a master plan to develop arotechnopark’s area in the village of Sei Buluh, potential, infrastructure and accesibilty of region, A good support, cooperation and coordination from the stakeholders are important factors to support the development of agrotechnopark’s area in North Sumatera. Keyword : agrotechnopark, criteria, region, management, strategy.